PREGNANCY AND CHILDBIRTH IN WOMEN OF DIFFERENT AGE GROUPS - Oblokulova O.A. (Western European Studies, 2025)
The age of the mother is one of the key factors determining the course of pregnancy, the nature of labor and outcomes for the mother and fetus. Current epidemiological data indicate an increase in both teenage and late pregnancy, which requires a differentiated approach in obstetric practice. This article presents the features of pregnancy and childbirth in women of different age groups, analyzes the main obstetric risks, perinatal complications, management tactics and current recommendations.
Keywords: pregnancy; childbirth; maternal age; teenage pregnancy